Nicotine in Vapor Exposure Decreases Hippocampal Neurons in Rats - Indrayani, Tsaniya Ahda; Hamidah Ikhwan, Salma Nur; Handayani, Ety Sari; Kuswati, Kuswati (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2024)
Background: Recently, many people have considered electronic cigarettes to be a safer alternative to conventional tobacco cigarettes, even though they still contain harmful substances such as nicotine, which is associated with a decrease in hippocampal neurons. Objective: This study aimed to examine the effect of exposure to e-cigarettes on hippocampal neurons in rats. Methods: An experimental study was performed using 26 tissue samples obtained from Wistar rats. The rats were randomly assigned to four groups and treated over an eight-week period as follows: the control group (K) (n=7) had no vapor exposure; the V0 group (n=6) received vapor without nicotine (0 mg/ml); the V6 group (n=7) was exposed to vapor and 6 mg/ml nicotine; and the V12 group (n=6) was exposed to vapor and 12 mg/ml nicotine. Hippocampal neurons were examined using hematoxylin-eosin staining at 400x magnification across 7 fields of view. Data were analyzed using the Kruskal-Wallis test with the Mann-Whitney post-hoc.  Results: The number of hippocampal neurons was significantly reduced in both the V12 and V0 groups compared to that in the control group (p<0.05). The lowest number of hippocampal neurons was observed in the V0 group (0 mg/ml nicotine), followed by the V12 group (12 mg/ml), and then the V6 group (6 mg/ml).Conclusion: The present study showed that the variation of nicotine in vapor exposure decreases hippocampal neurons in rats.